Avian haemosporidians from Neotropical highlands: Evidence from morphological and molecular data. Issue 4 (August 2015) - González, Angie D.; Lotta, Ingrid A.; García, Luis F.; Moncada, Ligia I.; Matta, Nubia E.
Abstract Avian haemosporidian parasites have been scarcely studied in the Neotropical highlands despite the high avian diversity reported and the uniqueness of these ecosystems. The aims of this study were to examine Haemoproteus and Plasmodium diversity based on morphological and molecular data, as well as to explore the concordance between these two approaches, when identifying species. We sampled 1487 birds belonging to 166 species, in localities of the Colombian Andean region at elevations ranging from 2100 to 4000 m above sea level. Here, we report twelve morphological parasite species, of which five are undescribed. Thirty parasite cytochrome b lineages are reported, 17 of which for the first time. We provide morphological information and illustrations, as well as, cytochrome b lineages for six morphospecies: Haemoproteus columbae, Haemoproteus witti, Haemoproteus coatneyi, Haemoproteus vireonis, Plasmodium lutzi, and Plasmodium unalis. This is the first report to provide a linkage between morphology and a molecular lineage for H. witti. Cytochrome b gene proved to be useful for species determination as DNA barcoding. Differences in parasite composition between lowlands and highlands in Colombia suggest a replacement of avian Plasmodium fauna. Parasite lineages restricted to either Colombian resident or Nearctic migratory birds were found; but a single lineage common in both has not been recorded in Nearctic non-migratory birds. We generated valuable information by using both morphological and molecular data representing competent host–parasite relationships which are based on observation of gametocytes in circulation; and increased the taxon sampling of avian haemosporidian.